The Niagara Effect: Reimagining Emotional Intensity in Young Adult Writing - Noah Weisz (Leaf Journal, 2023)
Contemporary Young Adult (YA) fiction often aims to capture and generate “emotional intensity,” which is held to be an inherent feature of the teenage experience. To produce this effect, YA authors frequently employ an expressive first-person voice, which is constructed as a mechanism for a certain “immediacy” facilitating the delivery of emotions in their rawest, most powerful form. However, some theorists and practitioners of fiction have pointed out that emotions are actually best evoked for the reader when conveyed in indirect ways. This suggests that the typical YA style may not always be the most effective path to achieving emotional intensity. This essay draws on a framework suggested by Joan Aiken in 1982 in order to open wider possibilities for YA writers to consider. Through an analysis of Julie Schumacher’s novel _Black Box_ in light of Aiken’s principles, and by contrasting it with Jandy Nelson’s novel _I’ll Give You the Sun_, the essay argues that overtly emotional first-person voices can sometimes actually prevent, rather than enable, emotional immediacy and intensity; and that creative attention to concrete detail and scene architecture, alongside a meticulous restraint of the first-person narrator’s own self-reflection and interpretation, can serve as remarkably potent alternative techniques.